Student partnership to achieve cultural change - Gamote, Shuab; Edmead, Leonie; Stewart, Bethany; Patrick, Tamara; Hamshire, Claire; Forsyth, Rachel (International Journal for Students as Partners, 2022)
This case study offers reflections on a student-led collaboration between the university and its student representative body (the Students’ Union) and outlines the successes and challenges of partnership to address institutional cultural change. The project was set up to improve students’ experiences and raise awareness of the existence of differential outcomes between Black, Asian, or minority ethnic (BAME) and white students and to promote strategies to build meaningful relationships through the development of internal and external networks. It was led by 11 BAME student ambassadors who developed and delivered campaigns and events for students and who linked with university staff and the Students’ Union to represent students’ views on ways to achieve positive change on campus. Partnership working was essential to enable the student ambassadors to develop trust, make their own changes, and influence key decision makers across the University.